Alveolar Ridge Preservation after Tooth Extraction Using Different Bone Graft Materials and Autologous Platelet Concentrates: a Systematic Review - Arturas Stumbras; Povilas Kuliesius; Gintaras Januzis; Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research)
Objectives: To review and assess the efficiency of different post extraction socket preservation techniques.